2020
DOI: 10.1007/s12520-020-01236-6
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the composition of historical remedies and pharmaceutical formulations: the identification of natural resins and balsams by gas chromatographic-mass spectrometric investigations

Abstract: The present paper reports one of the first studies on the identification of natural resins and balsams in modern era drug formulations. Gas chromatography coupled with mass spectrometry (GC-MS) was applied to investigate the composition of ancient remedies and pharmaceutical formulations coming from the Spezieria di Santa Maria della Scala in Rome, founded at the end of the seventeenth century by the Discalced Carmelites. The obtained results highlight the presence of complex mixtures containing resinaceous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Various methods are used for diagnosis of CD including small intestinal biopsy and serologic screening which are extremely profound and specific for antibodies. With the invention of quick screening techniques and knowledge of CD, many individuals are diagnosed including those who are asymptomatic [ 24 - 26 ].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods are used for diagnosis of CD including small intestinal biopsy and serologic screening which are extremely profound and specific for antibodies. With the invention of quick screening techniques and knowledge of CD, many individuals are diagnosed including those who are asymptomatic [ 24 - 26 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Histologic analysis in small intestinal biopsy indicates villous atrophy, intraepithelial lymphocytosis, and crypt hyperplasia. It also shows the presence of tissue transglutaminase enzyme (tTG), deamidated gliadin peptides (DGP), CD-specific antibodies, and endomysial antibodies (EMA) [ 24 ].…”
Section: Diagnosismentioning
confidence: 99%
“…These objectives were (1) to address the physicochemical characterization of the hundreds of drugs contained in the oldest containers at Santa Maria della Scala (which date from the late 17th century and early 18th century); (2) to conduct a historical and cultural study of the substances and recipes identified; (3) to study the geographical and temporal origin of these characterized medicinal treatments and explore their transmission and evolution through time; and (4) to complete the inventory and cataloguing of the personal property owned by this Roman spezieria. The results of the numerous research projects conducted at the spezieria over the last seven years (2016-2022) by the Department of Art History of the Universitat de València confirm that the Roman spezieria of Santa Maria della Scala is an ancient and historical mosaic of pharmaceutical knowledge [1][2][3][4][5][6]. These results have been possible thanks to the support provided by various national and international funding sources and to the scientific collaboration of universities, research centers and laboratories in Spain, Italy, France, Portugal and Switzerland, all of which responded in a coordinated manner to the objectives outlined in the first phase of the project (2016-2019).…”
Section: Introductionmentioning
confidence: 99%
“…This protocol consisted of a combination of microscopic techniques (Optical Microscopy/LM; Scanning Electron Microscopy-X-ray Microanalysis/SEM-EDX), diffractometry (X-ray Diffraction/XRD), spectroscopic techniques (Fourier Transform Infrared Spectroscopy/FT-IT; Raman Spectroscopy; and Nuclear Magnetic Resonance/NMR) and chromatographic techniques, isolated or in tandem (Gas Chromatography-Spectrometry of Mass/GC-MS, Pyrolysis-GC-MS, High-Performance Liquid Chromatography/HPLC). Finally, and always with the aim of improving the detection of organic compounds [4,6], work was conducted with Diffuse Reflectance (DR) and in-phase magnetic micro-extraction online "solid in tube" (Magnetic-IT-SPME) combined with capillary liquid chromatography-diode array detection (CapLC-DAD). The results obtained were analyzed from a historical and cultural perspective between 2019 and 2021 (Objectives 2,3).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, no visible traces of pitch were vis-ible on any of the studied objects. This analytical technique is frequently applied to archaeological organic residue in order to identify various molecules corresponding to terpenoids, notably diterpenic resinous materials from the Pinaceae family and acid molecules of wine [20][21][22] . The chemical analyses are based on the identification of diagnostic molecules of each natural product.…”
Section: Introductionmentioning
confidence: 99%